CNN Pincer Ruthenium Catalysts for Hydrogenation and Transfer Hydrogenation of Ketones: Experimental and Computational Studies. Issue 42 (4th September 2014) - Baratta, Walter; Baldino, Salvatore; Calhorda, Maria José; Costa, Paulo J.; Esposito, Gennaro; Herdtweck, Eberhardt; Magnolia, Santo; Mealli, Carlo; Messaoudi, Abdelatif; Mason, Sax A.; Veiros, Luis F.
Abstract: Reaction of [RuCl(CNN)(dppb)] (1‐Cl ) (HCNN=2‐aminomethyl‐6‐(4‐methylphenyl)pyridine; dppb=Ph2 P(CH2 )4 PPh2 ) with NaOCH2 CF3 leads to the amine‐alkoxide [Ru(CNN)(OCH2 CF3 )(dppb)] (1‐OCH2 CF3 ), whose neutron diffraction study reveals a short RuO⋅⋅⋅ HN bond length. Treatment of1‐Cl with NaOEt and EtOH affords the alkoxide [Ru(CNN)(OEt)(dppb)]⋅ (EtOH) n (1‐OEt⋅ n  EtOH ), which equilibrates with the hydride [RuH(CNN)(dppb)] (1‐H ) and acetaldehyde. Compound1‐OEt⋅ n  EtOH reacts reversibly with H2 leading to1‐H and EtOH through dihydrogen splitting. NMR spectroscopic studies on1‐OEt⋅ n  EtOH and1‐H reveal hydrogen bond interactions and exchange processes. The chloride1‐Cl catalyzes the hydrogenation (5 atm of H2 ) of ketones to alcohols (turnover frequency (TOF) up to 6.5×10 4  h −1, 40 °C). DFT calculations were performed on the reaction of [RuH(CNN′)(dmpb)] (2‐H ) (HCNN′=2‐aminomethyl‐6‐(phenyl)pyridine; dmpb=Me2 P(CH2 )4 PMe2 ) with acetone and with one molecule of 2‐propanol, in alcohol, with the alkoxide complex being the most stable species. In the first step, the Ru‐hydride transfers one hydrogen atom to the carbon of the ketone, whereas the second hydrogen transfer from NH2 is mediated by the alcohol and leads to the key "amide" intermediate. Regeneration of the hydride complex may occur by reaction with 2‐propanol or with H2 ; both pathways have low barriers and are alcohol assisted. Abstract : Ru stabilized : Solid state and solution studies show that the catalytically active pincer alkoxide‐amine ruthenium complexes are stabilized by hydrogen bonds (see figure) and reversibly give ruthenium hydride species by H elimination or H2 splitting. DFT calculations show that the pincer alkoxides are the most stable complexes, which rapidly form from the ruthenium hydride and carbonyl compounds through a non‐observable "amide" alcohol intermediate.